Workplace Cold and Perceived Work Ability: Paradoxically Greater Disadvantage for More vs. Less-Educated Poultry Industry Workers in Thailand - Phanprasit, Wantanee; Konthonbut, Pajaree; Laohaudomchok, Wisanti; Tangtong, Chaiyanun; Ikäheimo, Tiina M.; Jaakkola, Jouni J. K.; Näyhä, Simo (Frontiers in Public Health, 2021)
The association between worksite temperature and perceived work ability (WA) in various educational classes remains unknown. Therefore, we interviewed 286 poultry industry workers in Thailand about their WA and linked their responses to the worksite temperature. WA was based on the self-assessment of current work ability compared to their lifetime best ability (scores 0‒10). Education was classified as high (university or vocational school) or low (other education). Temperature was classified as cold (‒22 to 10°C) and warm (10 to 23°C). WA and the occurrence of low WA were regressed on worksite temperature, education and their interaction, adjusting for sex, age, job category, physical work strain, moving between cold and warm sites, thermal insulation of clothing, relative humidity and air velocity. The average worksite temperature was 10°C for high- and 1°C for low-educated workers. The average WA score was 8.32 (SD 1.33, range 4 to 10) and was classified as low (<8) in 23% of the workers. In highly educated workers, the adjusted WA declined from 9.11 in the warm areas to 8.02 in the cold areas, and the prevalence of low WA increased from 11% to 30%, while no significant change was observed in low-educated workers. The WA score was estimated to decline by 10% (95% CI 4 to 16) more in the cold areas in the high- than low-educated workers, and the prevalence of poor WA was estimated to increase 3.09 times (CI 1.43 to 5.45) more. Highly educated workers in this industry were identified as a risk group that should be given customised advice.